The effect of feeding Bt MON810 maize to pigs for 110 days on intestinal microbiota. - Stefan G Buzoianu (Public Library of Science (PLoS), 2012)
Objective To assess the effects of feeding Bt MON810 maize to pigs for 110 days on the intestinal microbiota. Methodology/principal findings Forty male pigs (∼40 days old) were blocked by weight and litter ancestry and assigned to one of four treatments; 1) Isogenic maize-based diet for 110 days (Isogenic); 2) Bt maize-based diet (MON810) for 110 days (Bt); 3) Isogenic maize-based diet for 30 days followed by a Bt maize-based diet for 80 days (Isogenic/Bt); 4) Bt maize-based diet for 30 days followed by an isogenic maize-based diet for 80 days (Bt/Isogenic). Enterobacteriaceae, Lactobacillus and total anaerobes were enumerated in the feces using culture-based methods on days 0, 30, 60 and 100 of the study and in ileal and cecal digesta on day 110. No differences were found between treatments for any of these counts at any time point. The relative abundance of cecal bacteria was also determined using high-throughput 16 S rRNA gene sequencing. No differences were observed in any bacterial taxa between treatments, with the exception of the genus Holdemania which was more abundant in the cecum of pigs fed the isogenic/Bt treatment compared to pigs fed the Bt treatment (0.012 vs 0.003%; P≤0.05). Conclusions/significance Feeding pigs a Bt maize-based diet for 110 days did not affect counts of any of the culturable bacteria enumerated in the feces, ileum or cecum. Neither did it influence the composition of the cecal microbiota, with the exception of a minor increase in the genus Holdemania. As the role of Holdemania in the intestine is still under investigation and no health abnormalities were observed, this change is not likely to be of clinical significance. These results indicate that feeding Bt maize to pigs in the context of its influence on the porcine intestinal microbiota is safe.